Efficacy and safety of peroxide-based mouthrinse on whitening treatment: A randomized controlled clinical trial - Mailart, Mariane Cintra [UNESP]; Carvalho dos Santos, Karine [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Borges, Alessandra Bühler [UNESP] (Elsevier, 2025)
Objectives: This randomized controlled clinical trial evaluated the efficacy and safety of peroxide-based mouthrinse on whitening treatment. The patient's satisfaction and treatment longevity were also assessed. Material and methods: Participants (N = 45) were randomly allocated to three different groups: WM (Whitening mouthrinse – 2.5% hydrogen peroxide); PM (Placebo mouthrinse – 0% hydrogen peroxide); and WG (Whitening gel - 10% carbamide peroxide). The treatment was performed twice daily for 30 s over 90 days for WM and PM and once daily for 2 h over 14 days for WG. Tooth color was evaluated with shade guides (ΔSGU) and with a spectrophotometer (ΔE00 and WID) after 14, 30, 60, 90, 120 days, and 2 years. Tooth sensitivity, gingival condition, and patient satisfaction were also evaluated. Results: WG resulted in the highest color change over time for visual (ΔSGU) and objective (ΔE00 and WID) analyses. With WM, significant visual color alteration was detected in the 60-day assessment compared with PM. After 2 years, no color rebound was observed for the treatments. A very low intensity of sensitivity was found for WM and WG. No gingival irritation was detected. All the participants were satisfied with the whitening treatment outcomes. Conclusions: The peroxide-based mouthrinse effectively changed tooth color, with relevant effect detected after 60 days of use. However, the whitening result obtained with the conventional carbamide peroxide gel treatment was more pronounced. No relevant adverse effects were observed, and the outcomes were maintained for 2 years. Clinical significance: Peroxide-based mouthrinse is an effective alternative whitening treatment, although it promotes less color change compared with the conventional at-home technique without inducing significant adverse effects. Patients should be warned about the prolonged treatment and the need for compliance.
Keywords: At-home bleaching; Clinical trial; Hydrogen peroxide; Tooth color; Tooth sensitivity; Whitening mouthrinse